Ethics And Integrity In A Public Sector Organisation In Malaysia: An Assessment Of Understanding And Perception Of The Employees - Izawati Wook; Dato' Hasnah Hj Haron; Rosli Shaari; Zulkiple Abd Ghani; Abd Hakim Mohad @ Mohamad Ramli; Arif Fahmi Md Yusof (Penerbit Universiti Malaysia Pahang, 2024)
VOL. 5 NO. 3 (2022) Page (382-392)